Measurement of Intracellular Ions by Flow Cytometry. Issue 1 (1st April 2015) - Posey,, Avery D.; Kawalekar, Omkar U.; June, Carl H.
Abstract: Using flow cytometry, single‐cell measurements of calcium can be made on isolated populations identified by one or more phenotypic characteristics. Most earlier techniques for measuring cellular activation parameters determined the mean value for a population of cells, which did not permit optimal resolution of the responses. The flow cytometer is particularly useful for this purpose because it can measure ion concentrations in large numbers of single cells and thereby allows ion concentration to be correlated with other parameters such as immunophenotype and cell cycle stage. A limitation of flow cytometry, however, is that it does not permit resolution of certain complex kinetic responses such as cellular oscillatory responses. This unit describes the preparation of cells, including labeling with antibodies and with calcium probes, and discusses the principles of data analysis and interpretation. © 2015 by John Wiley & Sons, Inc.